Clinical Variations Between Different Forms of Achalasia - Sánchez Terán, Alfonso Iván; Naranjo Pardo, Catalina; Varela Barraza, Omar; Prado Salcedo, Tatiana; Macías Grajeda, Michelle (International Journal of Innovative Research in Medical Science, 2023)
Background: Esophageal achalasia is a motility disorder characterized by a lack of esophageal peristalsis and failure of the lower esophageal sphincter (LES) to relax. Patients typically present dysphagia for both solids and liquids, regurgitation, retrosternal chest pain, cough, aspiration, weight loss and heartburn, which affect their quality of life. Objective: To determine whether the High-resolution manometry (HRM) achalasia subtypes could be differentiated based on symptoms or radiographic findings. Methods: A cross-sectional study design was used, and data collected from 60 patients between 18 and 65 years and a diagnosis of achalasia using HRM over a period of ten years. The symptom assessment was done in a clinical interview using three international questionnaires for esophageal symptoms. Results: The mean symptom duration for the 3 groups was 25.03 ± 24.88 months, type I 25 ± 22.76 months and type II 24.98 ± 27.32 months, type III had a median of 27 (18-36) months. The mean esophageal diameter of patients with achalasia was 4.87 ± 1.48 cm. Type I had the greatest dilation (5.37 ± 1.7 cm) when compared to type II (4.46 ± 1.03 cm) and to type III 2.75 (2-3.5) cm. The mean esophageal length of all achalasia patients was different among the groups; type I 24.19 ± 2.96 cm and type II 22.96 ± 2.23 cm, type III had a median of 20.63 (20.13-18.13) cm. Conclusions: Despite the difference in degree of dilation between the subtypes, symptom duration does not appear to be correlated to the pattern of the achalasia.